Photothermal study of doped ZnO ceramics - Zakaria, Azmi; Rizwan, Zahid; Hashim, Mansor; Shaari, Abdul Halim; Mat Yunus, Wan Mahmood (Universiti Putra Malaysia Press, 2005)
Photopyroelectric spectroscopy (PPES) is used to study the band-gap energy, Eg, of ZnO doped with 1 mol% MnO and 0 – 2.0 mol% of Er2O3 sintered at isothermal sintering temperatures, 1200 and 1300⁰C. The wavelength of incident light is kept in the range from 300 to 800 nm and the PPE spectrum with reference to the doping level and sintering temperature is discussed. Eg were estimated from the plot (ρhυ)2 vs hυ and the values are 2.12, 2.09 eV for the samples sintered at 1300 ⁰C, 1200 ⁰C, respectively, for 0 mol% of Er2O3 doping level. Eg becomes constant with the fluctuation about 1.8 % at all doping levels of Er2O3 mol% indicating that the interfacial states are not produced further in MnO-ZnO ceramics by Er2O3 mol%. The decrease in steepness factor is related to sintering temperature and Er2O3 mol%. The X-ray diffractrometry shows that the crystal structure of ZnO doped with 1 mol% of MnO and different mol% of Er2O3 at all sintering temperatures remains to be of hexagonal type but peaks of Er2O3 are prominent. Small peaks of new phases Mn2O3 and ZnMnO3 are observed in the XRD pattern. Microstructure, compositional analysis of the selected areas is observed by SEM and EDAX. The clusters of Er2O3 are observed at nodal points. Density increases from 87.2 to 91.9 % and 80.6 to 88.7 % of the theoretical density (5.78 g/cm3) of pure ZnO at sintering temperatures 1200 and 1300 ⁰C, respectively, with the increase of Er2O3 mol%.